Pengaruh Karakterisitk Perusahaan dan Good Corporate Governance terhadap Praktik Pengungkapan Sustainability Report (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2011-2015) - Suryaningsih, Ayuk, Dra. Rina Trisnawati, M.Si, Ak, Ph.d (2017)
This study aims to analyze the effect of profitability, liquidity, leverage, company size, the number of audit committee meetings and the number of board meetings on sustainability report disclosure. The population of this research is manufacturing companies listed on the Stock Exchange in 2011-2015. The total sample is 32 companies were determined by purposive sampling. Data analysis use logistic regression. The results of this study indicate that factors characteristic of companies is profitability, liquidity and company size have effect on sustainability report disclosure, while leverage, number of audit committee meetings and the number of board meetings does not effect on sustainability report disclosure. Keywords: sustainability report, profitability, liquidity, leverage, company size, the number of audit committee meetings, the number of board meetings.